Tantangan dan Peran Digital Forensik dalam Penegakan Hukum terhadap Kejahatan di Ranah Digital - Amsori; Awaluddin, Fakhri; Mulyana, Momon (PT Elaborium Elevasi Indonesia, 2024)
Significant transformations in human interaction patterns have occurred thanks to advances in science and technology in the field of communication technology. The era of information technology began with the emergence of computer innovation, which initially came in the form of mainframe computers. Advances in information and communication technology have brought major changes to social interaction and human civilization globally. The use of information technology raises cyber law and cybercrime as important issues. Technological developments have commensurate consequences, with benefits in everyday activities but also negative impacts through online fraud and cybercrime. In handling information technology crime cases, digital forensics has an important role, especially in facing evidentiary challenges. Digital forensics includes the analysis of digital traces and has become an integral part of law enforcement in the digital era. The formation of the Indonesian Digital Forensics Association and the Electronic Transaction Information Law confirms the urgency of digital forensics in law enforcement in Indonesia.